Knowledge, Attitude, and Practice of General Population toward Complementary and Alternative Medicines in Relation to Health and Quality of Life in Sungai Petani, Malaysia - Syed G Mohiuddin; Sohail Aziz; Muhammad Z Iqbal; Atta A Naqvi; Rizwan Ahmed; Mansour A Mahmoud; Syed A Ghori (Wolters Kluwer Medknow Publications, 2020)
Purpose: The demand of complementary and alternative medicine (CAM) has increased drastically over the past few decades. The perceptions about CAMs among general population are positive. However, the literature highlights that effectiveness and acceptance of alternative therapies among the general population is still a subject of debate. Materials and Methods: This is a cross-sectional study and the response along with demographic details was collected through a validated questionnaire; the results were analyzed by using a validated data collection tool. The results were concluded based on good, moderate, and poor responses, which were evaluated through data analysis by using the Statistical Package for the Social Sciences software version 20.0., SPSS Inc., Chicago, III, USA. A value of P < 0.05 was considered statistically significant. Results: In total, 182 (44.4%) of male and 228 (55.6%) of female respondents were selected for this study. Studies showed that a greater knowledge level was observed among female respondents (15.55 ± 2.7, P < 0.001). The selected Chinese population had relatively good knowledge (i.e., 15.63, P = 0.006). People practicing Buddhism had also good knowledge. Rural population had lesser family income and showed a good practice pattern and understanding (P = 0.006). The positive attitude was identified among women ( P < 0.001) with a mean score of 15.55 ± 2.7. Postgraduate participants were found to have diverse results with SD ± 6.23, and 77.1% had a good attitude. A statistically significant association was observed between religion and attitude of respondents (P < 0.001). Conclusion: Although a better practice was noticed in Malaysian population, more awareness is required and knowledge should be disseminated among the population to improve the overall health and quality of life in Malaysia.